Public-private partnerships in physical activity and sport - O'Reilly, Norm 1973-; Brunette, Michelle K. 1978- (Champaign, IL Human Kinetics, 2013)
Public-Private Partnerships in Physical Activity and Sport is a guide for non-profit, charity, and sport organizations in developing and maintaining strategic and responsible relationships with corporate partners. With its comprehensive and practical examination, this text is also relevant to private sector corporations seeking public sector partners and for agencies seeking to broker such partnerships. This text is drawn from the collaboration of leaders in public and private organizations, athletes, and academics who identified a need to provide formalized direction on partnerships between the public and private sectors. Authors O'Reilly and Brunette present a detailed discussion of the pros and cons of establishing partnerships between not-for-profits and private sector organizations. They also provide a thorough understanding of the issues and illustrate how a responsible implementation of these partnerships can benefit all parties involved. They offer strategies and tactics for finding, developing, implementing, and evaluating public-private partnerships and highlight how partnership and social marketing studies outside of public health and health promotion can inform these growing disciplines. Public-Private Partnerships in Physical Activity and Sport is part of the Physical Activity Intervention Series. This timely series provides educational resources for professionals interested in promoting and implementing physical activity programs to a diverse and often resistant population.
Finding consensus in how to develop partnerships -- The partnership protocol -- The basics of messaging and marketing in physical activity and health -- The value of sponsorship in physical activity and health -- Fundraising (working title) -- Philanthropy (working title) -- Role models in physical activity, sport participation, and health : the case of Elia Saikaly and finding life -- Partnership champions -- Leveraging corporate social responsibility (CSR) to partner with corporations -- Partnership perspectives : global, national, community -- Applying partnership guidelines in physical activity and health -- Challenges in creating effective partnerships : bias, controversy, failure.
Includes bibliographical references (p. 213-221) and index.
Keywords: Physical Fitness; Exercise; Health Promotion; Public-Private Sector Partnerships; Sports